Rules for contrast sets - Azevedo, Paulo J. (2010)
In this paper we present a technique to derive rules describing contrast sets. Contrast sets are a formalism to represent groups diferences. We propose a novel approach to describe directional contrasts using rules where the contrasting efect is partitioned into pairs of groups. Our approach makes use of a directional Fisher Exact Test to and significant diferences across groups. We used a Bonferroni within search adjustment to control type I errors and a pruning technique to prevent derivation of non significant contrast set specializations.